The Role of Law in Regulating Compulsory Vaccination: Between Human Rights and State Obligations during the Pandemic - Yuwono, Lila Graciella; Kansil, Christine S T (CV. Rayyan Dwi Bharata, 2024)
Public health protection is one of the main obligations of the state in an effort to maintain the welfare of its citizens. One of the policies implemented is mandatory vaccination to reduce the spread of infectious diseases and maintain collective health. However, this policy raises challenges in terms of balancing between the state's responsibility to protect the community and individual human rights, especially the right to determine which medical interventions to accept. This research aims to examine the role of law in regulating mandatory vaccination in Indonesia, as well as how the policy can be implemented without violating human rights. This study uses a normative juridical approach by exploring various regulations that form the basis for the implementation of mandatory vaccination in Indonesia, including Law Number 36 of 2009 concerning Health and Presidential Regulation Number 99 of 2020 concerning Vaccine Procurement and Vaccination Implementation. The analysis shows that compulsory vaccination has a strong legal footing to protect public health, but it must still respect individual rights, especially the right to choose medical interventions. The state is also required to ensure that this policy is implemented in a fair and non-discriminatory manner, especially for vulnerable groups such as children, the elderly, and individuals with special health conditions. This study also found that adequate education and socialization are important factors to increase public acceptance of mandatory vaccination. Public opposition is generally caused by a lack of proper understanding of the benefits of vaccines, as well as the spread of inaccurate information about vaccine safety. Therefore, a more persuasive approach, involving community leaders and related institutions, is needed to provide better understanding and increase public trust in vaccination policies. Mandatory vaccination policies need to be implemented while maintaining a balance between the state's obligation to protect public health and human rights. Not only does the state need to strengthen the legal basis for vaccination, but it must also ensure that this policy is implemented in a fair and inclusive manner.